INTERNAL AND EXTERNAL FACTORS OF DIVIDEND PAYOUT POLICY: EVIDENCE FROM MALAYSIAN CONSTRUCTION SECTOR - MUHAMMAD HAFIZ ALI; NORHUDA ABDUL RAHIM School of Business and Economics; MOHAMED HISHAM YAHYA School of Business and Economics (Journal of Academia, 2021)
This study is set to identify the internal and external determinants of dividend policy of Malaysian listed construction firms. In specific, this study (1) investigates which determinants strongly explain dividend policy’s proxy and (2) identifies the relationship between firms’ internal and external determinants with dividend policy’s proxy. This study’s specification model is developed using the Dividend Smoothing Theory. Four firms’ internal factors (EPS, SIZE, lagDIV, FCFps) and one firms’ external factor (MBeta) are investigated. Panel data regression analysis of Ordinary Pooled Least Squares, Fixed Effects Model and Random Effects model are used to investigate the identified factors. The findings highlight that the Fixed Effects Model is the most appropriate, with an explanatory power of 33.73%. Three firms’ internal factors variables (EPS, lagDIV, and FCFps) are significant and positively affect firms’ dividend policy. This study also investigates other empirically proven firm’s factors and found that they are not significant. Furthermore, they worsened the model’s explanatory power. Thus, proving a unique difference in dividend policy’s predictors of the different economic sectors.